Tradíció és reprezentáció két 17. századi debreceni neolatin gyászvers-antológiában - Posta, Anna (Studia Litteraria, 2021)
The focus point of my study evokes the poetic rhetorical tradition of the early modern death poetry. At the beginning I would like to review the metric characteristics and the genres of mourning poems rooted in antiquity, then trough the rhetorical shapes, allusions, and tropics of the verse texts that are the subject of my analysis, I will point out the connection of the funeral poems with the classic literary patterns. At the end of my study anthologies will be analyzed from the perspective of representational gestures appearing in death poems. e poems include the representation of the departed and the weeping community as well. The poems emphasize the most important moments of the departed, his turning point events, the characteristics of the individual that are worthy of recognition and praise, his merits or just the important historical events of the given era. At the same time the micro and macro-structure related to the 17th century intelligentsia is drawn from the varied composition of the volumes, as well as the connection of the people living in Debrecen with the other members of the diocese. The lyrical speakers say goodbye mostly on the behalf of the community (family, friends, school, church, home) interpreting death as a collective loss.